2018
DOI: 10.1055/s-0038-1675203
|View full text |Cite
|
Sign up to set email alerts
|

Do-It-Yourself Microsuture from Human Hair for Basic Microsurgical Training

Abstract: Background Microsuture is an essential material for basic microsurgical training. However, it is consumable, expensive, and sometimes unavailable in the microsurgical laboratory. To solve this problem, we developed a microsuture made from human hair and needle gauge. Methods Do-It-Yourself (DIY) microsuture is made from human hair and needle gauge 32G (BD Ultra-Fine Pen Needles 4 mm × 32G). Methods are explained step by step. This DIY microsuture (labeled as “test microsuture”) and nylon 8–0 (Ethil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The nylon 8-0 and 10-0 suture materials used in this study were approximately 50% of the total cost. To reduce this expense, some studies have demonstrated that human hair can be used as a replacement for nylon sutures in microsurgical training [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nylon 8-0 and 10-0 suture materials used in this study were approximately 50% of the total cost. To reduce this expense, some studies have demonstrated that human hair can be used as a replacement for nylon sutures in microsurgical training [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thermoplastic films from the features were created and analysed, with the results revealing that the feather films were water resistant and strong [ 104 , 105 , 106 , 107 , 108 , 109 ]. This could be utilised to make biomaterials for a variety of biomedical applications [ 110 , 111 , 112 , 113 ]. Human hair has sufficiently high strength for use as sutures in most surgeries.…”
Section: Applications Of Animal Fibersmentioning
confidence: 99%
“…describe the use of human hair and insulin needles (BD Ultra-Fine Pen Needles 4 mm × 32 G, expresschemist.co.uk, £0.13 each) to make homemade microsurgical sutures ( Table 1 ). Feedback from trainees in their study suggested that human hair sutures ( Figure 1 ) was a “good-excellent” standard for microsurgical practice, equal to that of standard sutures 3 . This is reflected in our experience; we find that a hair of dark colour, mid length, coarse texture and wavy consistency works best.…”
mentioning
confidence: 99%